Building the Foundation for Healthy Societies : Influencing Multisectoral Action for Health, Phase One, Volume 1. Multisectoral Opportunities and Constraints Assessment Tool - Pierre-Louis, Anne M.; Harman, Neesha; Meiro-Lorenzo, Montserrat; Lutalo, Martin; Pascual, Brian; Davies, Maggie (2016)
The KP aims to support the Bank in adopting a significantly more systematic approach to multisectoral action in countries to maximize investment in other sectors for health results, in line with its comparative advantage. It will help to meet the Bank s twin goals and add value to its work in countries, by providing task teams with data on the burden of disease and risks and their upstream determinants, which multisectoral action could address, toward the goal of reducing poverty. It will assist in demonstrating the links between upstream determinants, such as poverty and inequality, and health outcomes. KP will identify proven and cost-effective multisectoral solutions from international best practice that have the potential for transferability to local contexts. It will then help understand the drivers, opportunities and constraints of work across practices and sectors on a common agenda to meet the Bank s goals. Finally, contributing to the effective delivery of existing Bank work across sectors within countries, and provide foresight and priorities for future action.